Safety and feasibility of preoperative exercise training during neoadjuvant treatment before surgery for adenocarcinoma of the gastro‐oesophageal junction. Issue 1 (24th October 2018) - Christensen, J. F.; Simonsen, C.; Banck‐Petersen, A.; Thorsen‐Streit, S.; Herrstedt, A.; Djurhuus, S. S.; Egeland, C.; Mortensen, C. E.; Kofoed, S. C.; Kristensen, T. S.; Garbyal, R. S.; Pedersen, B. K.; et al.
Abstract : Background: Neoadjuvant chemotherapy or chemoradiotherapy is used widely before tumour resection in cancer of the gastro‐oesophageal junction (GOJ). Strategies to improve treatment tolerability are warranted. This study examined the safety and feasibility of preoperative exercise training during neoadjuvant treatment in these patients. Methods: Patients were allocated to a standard‐care control group or an exercise group, who were prescribed standard care plus twice‐weekly high‐intensity aerobic exercise and resistance training sessions. The primary endpoint was the incidence of serious adverse events (SAEs) that prevented surgery, including death, disease progression or physical deterioration. Preoperative hospital admission, postoperative complications, changes in patient‐reported quality of life and pathological treatment response were also recorded. In the exercise group, adherence to exercise and changes in aerobic fitness, muscle strength and body composition were measured. Results: The incidence of SAEs was not increased in the exercise group. The risk of failure to reach surgery was 5 versus 21 per cent in the control group (risk ratio (RR) 0·23, 95 per cent c.i. 0·04 to 1·29), the risk of preoperative hospital admission was 15 versus 38 per cent respectively (RR 0·39, 0·12 to 1·23) and the risk of postoperative complications was 58 versus 57 per cent (RR 1·06, 0·61 to 1·73). The exercise group attended a mean of 17·5 sessions, and improved fitness, muscle strength and Functional Assessment of Cancer Therapy — Esophageal (FACT‐E) total score compared with the baseline level. Conclusion: Preoperative exercise training during neoadjuvant treatment in patients with GOJ cancer is safe and feasible, with improvements in fitness, strength and quality of life. Preoperative exercise training may be associated with a lower risk of critical SAEs that preclude surgery or result in hospitalization. Abstract : This feasibility study shows that preoperative exercise training is feasible and leads to favourable changes in fitness, strength and quality of life in patients with cancer of the gastro‐oesophageal junction. These exercise adaptations may be associated with lower risk of treatment failure and hospitalization, which could have important implications for future perioperative management. [Correction added on 25 October 2018, after first online publication: the FACT‐E score has been corrected to + 2 points for the control group] Seems to work